Thermally activated shape memory behavior of copolymers based on ethylene reinforced with silica nanoparticles - Valentina Sessini (Taylor & Francis Group, 2018)
In this work, a study on the dual-shape and triple-shape memory response of poly(ethylene-co-methacrylic acid) copolymer, EMAA, and its counterpart neutralized with sodium salt, EMAA-Na has been report. Moreover, both matrices were reinforced with silica nanoparticles in different amount. Morphological, thermal and mechanical properties were studied confirming the good dispersion of the nanoparticles into both polymeric matrices. The addition of silica nanoparticles increases the mechanical response of both polymeric matrices without affecting their shape memory response leading to a possible increasing use of both polymers in the industry. Moreover, the ionomeric polymer reinforced with 1 wt.% silica nanoparticles present excellent thermally activated triple-shape memory response.